PERAN KEPALA DESA DALAM MENGEMBANGKAN BADAN USAHA MILIK DESA DI DESA MERANTI BUNTING KABUPATEN KEPULAUAN MERANTI - Neirista Aisyani; Dessy Artina; Evi Deliana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
This study aims to determine the Management of Village-Owned Enterprises(BUMDes) in Meranti Bunting Meranti Islands Village, and to determine the factors thatinfluence the Management of Village-Owned Enterprises (BUMDes) in Meranti BuntingMeranti Islands Village based on Government Regulation of the Republic of IndonesiaNumber 11 Year 2021 Concerning Village-Owned EnterprisesThis research is a sociological book research because it is based on field research,namely by collecting data from observations, interviews, and literature studies that provide arelationship with the problem assisted by primary, secondary, and tertiary data. The type ofresearch data is descriptive qualitative research. This research looks at the Role of theVillage Head in the Implementation of Village Owned Enterprises in Meranti Bunting Village.The data sources are primary and secondary data, the number of informants in this study is 6informants then draws the final conclusions from the interview results.Based on the research results, it can be seen that the Management of Village-OwnedEnterprises in Meranti Bunting Meranti Islands Village has 4 aspects that affect management,namely the Planning Aspect. In the Planning Aspect, BUMDes Meranti Bunting Village hasfollowed the procedures listed in the AD/ART and planned programs to be implemented andmanaged along with the budgets to be used and managed by BUMDes Meranti BuntingVillage. Second, Organizing, Meranti Bunting Village BUMDes appoint managers who areelements of the Meranti Bunting Meranti Islands Village community and do not have duties inVillage Government and in building good work communication cooperation is needed inorder to achieve a business unitary and organizational goals Third Direction, in achievingtargets according to the planning in the management of BUMDes Meranti Banting MerantiIslands Village the manager has directed and supervised the work of members who joined andmonitored so that they can achieve success in managing BUMDes in Meranti BuntingMeranti Islands Village. Evaluation Committee, in evaluating the results of the work ofmanagers and the community continues to carry out evaluations every 3 months, every 6months and annually. At the evaluation stage BUMDes Meranti Bunting Meranti IslandsVillage continues to carry out transparency of funds so that there are no misunderstandingsand problems. Then the factors that influence the management of Meranti Bunting MerantiIslands Village are the cooperation system to full support by the Village Government, equityand procurement of BUMDes business funds, but development cannot be said to be successfulbecause the management of BUMDes is still experiencing bottlenecks in the issue of capitalparticipation funds.Keyword : The role of-village head-village owned enterprises